The Rise of Faith-Based Welfare Providers in Germany and Its Consequences - Josef Hien; Sascha Kneip (German Politics, 2020)
Since the 1970s welfare organisations operated by the churches in Germany have evolved into the country's largest employers. While church affiliation and attendance dropped sharply, the churches grew as employers. Caritas and Diakonie, the two largest faith-based welfare providers, enjoy a special status as ecclesiastical employers. They can dismiss employees that do not live in congruence with their worldview such as homosexuals, those who have re-married or those who exit the church. Moreover their employees are exempted from the right to strike. The following is the first study that offers a comprehensive analysis of the phenomenal rise of faith-based welfare providers in Germany and the consequences of their special status for employees. The encompassing analysis of labour-law conflicts in German courts between ecclesiastical employers and their employees shows that the contentiousness of those controversies has increased over time. We explain this with the changed composition in the workforce of Caritas and Diakonie which has, in contrast to former times, today much less connection to the values of the church. Moreover, our analysis of legal cases shows that Caritas and Diakonie so far have been able to successfully defend their special status in front of German courts.
Keywords: 300